THE EFFECT OF LIQUIDITY, ASSET MANAGEMENT AND INTERNAL MANAGEMENT ON DIVIDENDS DISTRIBUTION DECISIONS WITH PROFITABILITY AS MODERATOR VARIABLES IN MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Shella Shella; Angeline Angeline; Jennifer Jennifer; Namira Ufrida Rahmi (Jurnal Ekonomi, 2022)
This study aims to analyze the effect of liquidity, asset management and internal management on dividend distribution decisions with profitability as moderator variable in manufacturing companies listed on the Indonesia Stock Exchange. This study uses associative which shows the relationship between the independent variable and the dependent variable. The population of this study amounted to 192 Manufacturing Companies listed on the Indonesia Stock Exchange for the 2017-2020 period . company and obtained a sample of 44 data from purposive sampling technique. Multiple linear regression analysis technique . The result of this research is that liquidity has an effect on dividend distribution decisions in manufacturing companies listed on the Indonesia Stock Exchange. Asset Management Affects Dividend Distribution Decisions on Manufacturing Companies listed on the Indonesia Stock Exchange. Internal Management has no effect on the decision to distribute dividends to manufacturing companies listed on the Indonesia Stock Exchange. Profitability has no effect on the decision to distribute dividends in manufacturing companies listed on the Indonesia Stock Exchange. Profitability is not able to moderate and strengthen the influence of liquidity, asset management and internal management on dividend distribution decisions in Manufacturing Companies listed on the Indonesia Stock Exchange.